PROJECT CITIZEN LEARNING MODEL BASED ON PORTFOLIO FOR EDUCATION COMPETENCE TOWARDS SOCIETY 5.0 - Helminsyah Helminsyah; Musdani Musdani; Ali Mustadi; Anwar Monday (Jurnal Ilmiah Teunuleh, 2021)
This research intends to develop a portfolio-based project citizen model to strengthen the social competence of educators towards society 5.0. This research design uses the Research and Development method in this research in grade IV elementary schools in SDN City, Banda Aceh, teachers, and learning experts. Information is combined with methods of monitoring, in-depth debriefing, and selection. Information analysis was tried by quantitative methods, namely descriptive and comparative. The results obtained are the acquisition of Measuring competence and the acquisition of a quality learning model The results of the expert's assessment of the quality of the Portfolio display number 3, 38 (in good type), from the quality of the form it proves the number 3.04 (in good type), on the contrary from the point of view of organizing the module the score is: stability of 2.92 (pretty good), shape of 3, 13 (good), organization of 3, 25 (good), shape and dimensions of 2, 63 (pretty good) The results of the feasibility trial (trial) on students prove the quality of proving the number 3, 28 (in good type), From the quality of form and energy, it proves that the score is 3.30 (in good category), on the contrary from the organizing part of the module, the score is: 3.22 (good). Thus, the portfolio-based Project citizen model to strengthen the social competence of educators towards society 5 is feasible to use.